Sheet metal coil processing - Cook, Jerome T.; Green, Richard G.; Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2003)
This program introduces the primary methods of processing sheet metal coils, featuring segments on coil slitting, coil blanking, and coil processing lines that focuses primarily on the equipment and methods of feeding of coil stock stamping presses and other processing lines
Code no : DV03PUB30
Title from title screen
Executive producer, Steven R. Bollinger ; graphics, Dennis Summers, Quantum Dance Works, Jerome T. Cook ; video editing, Jim O'Donnell
Keywords: Sheet-metal work; Metal -- cutting; Metals; Slitting (Metal-work)